Single-stage tibial osteotomy for correction of genu varum deformity in children - Kolbe, Nikolas; Haydon, Frank; Kolbe, Johannes; Dreher, Thomas (Children, 2023)
Conservative and operative treatments with gradual or acute correction of severe varus deformities of the leg have been described. We evaluated whether the corrective osteotomy used within the NGO Mercy Ships is an effective treatment for genu varum deformity of different etiologies in children and which patient specific factors have an influence on the radiographic outcome. In total, 208 tibial valgisation osteotomies were performed in 124 patients between 2013 and 2017. The patients’ mean age at the time of surgery was 8.4 (2.9 to 16.9 (min/max)) years. Seven radiographically measured angles were used to assess the deformity. Clinical photographs taken pre- and postoperatively were assessed. The mean time between the surgery and the end of physiotherapeutic treatment was 13.5 (7.3 to 28) weeks. Complications were monitored and classified according to the modified Clavien-Dindo-classification system. The mean preoperative mechanical tibiofemoral angle was 42.1° varus (range: 85°-12° varus). The mean postoperative mechanical tibiofemoral angle was 4.3° varus (range: 30° varus-13° valgus). The factors predicting a residual varus deformity were higher age, greater preoperative varus deformity and the diagnosis of Blount disease. The tibiofemoral angle measured on routine clinical photographs correlated well with the radiographic measurements. The single-stage tibial osteotomy described is a simple, safe and cost-effective technique to correct three-dimensional deformities of the tibia. Our study shows very good mean postoperative results, but with a higher variability than in other studies published. Nevertheless, considering the severity of preoperative deformities and the limited opportunities for aftercare, this method is excellent for the correction of varus deformities.